2022
DOI: 10.1021/acsami.2c13035
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Transparent, and Hazy Composite Cellulosic Film with Interconnected Silver Nanowire Networks for EMI Shielding and Joule Heating

Abstract: An optical transparent and hazy film with admirable flexibility, electromagnetic interference (EMI) shielding, and Joule heating performance meeting the requirements of optoelectronic devices is significantly desirable. Herein, a cellulose paper was infiltrated by epoxy resin to fabricate a transparent cellulose paper (TCP) with high transparency, optical haze, and favorable flexibility, owing to effective light scattering and mechanical enhancement of the cellulose network. Moreover, a highly connected silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 49 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…28,29 In our previous study, we reported the fabrication of interconnected AgNWs with welded junctions via thermal annealing at 150 °C for 1 h. The interfacial resistance decreased significantly and improved the EMI shielding performance of the composite film. 30 Nevertheless, thermal treatment might induce the oxidation of AgNWs and damage heat-sensitive substrates. Therefore, it is required to develop an effective and scalable method to improve the contact of wire− wire junctions in the absence of high heating temperatures, chemical reagents, or specific equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 In our previous study, we reported the fabrication of interconnected AgNWs with welded junctions via thermal annealing at 150 °C for 1 h. The interfacial resistance decreased significantly and improved the EMI shielding performance of the composite film. 30 Nevertheless, thermal treatment might induce the oxidation of AgNWs and damage heat-sensitive substrates. Therefore, it is required to develop an effective and scalable method to improve the contact of wire− wire junctions in the absence of high heating temperatures, chemical reagents, or specific equipment.…”
Section: Introductionmentioning
confidence: 99%
“…A satisfactory EMI shielding ability requires high electrical conductivity via suitable AgNW loading, which inevitably reduces the optical transmittance of AgNW-based transparent EMI shielding materials. It is imperative to develop an efficient strategy to simultaneously increase the optical transmittance and conductivity of transparent EMI shielding materials by reducing the interfacial resistance of neighboring nanowires. , In our previous study, we reported the fabrication of interconnected AgNWs with welded junctions via thermal annealing at 150 °C for 1 h. The interfacial resistance decreased significantly and improved the EMI shielding performance of the composite film . Nevertheless, thermal treatment might induce the oxidation of AgNWs and damage heat-sensitive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…As the base of flexible electronics, a silver nanowire (AgNW) transparent electrode has broad application prospects. For practical application, the uniformity of the transparent electrode is important. To promote the uniformity of AgNW transparent electrode, researchers have developed many excellent strategies. First, researchers improve the wettability between the ink and the substrate. , Specific methods include adjusting the surface tension of the ink and substrate by the following methods: ozone activation, corona treatment, binder coating, adding surfactant or low-surface-tension material, etc. Second, the drying process is carefully controlled to relieve the problem of coffee ring and punctate film. Third, the film-preparation technology (ink dosage, coating speed, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanowires (AgNWs) have been used in a wide range of applications in recent years due to their excellent aspect ratio and good electrical conductivity, including flexible fuel cells, stretchable and transparent supercapacitors, transparent sensors, , air filters, , color changing soft robotics, and flexible and transparent EMI shielding films. Wang et al used a simple rod coating method to embed AgNW layers in gelatin. By controlling the concentration of the AgNW layer in the AgNW layer, a flexible film with a visible light transmittance of 72% and an EMI shielding effectiveness of 37.7 dB was obtained.…”
Section: Introductionmentioning
confidence: 99%